Assessment of Glial Fibrillary Acidic Protein Binding to the Surface of Leukocytes with Dark‐Field Imaging and Computational Analysis. (20th January 2021) - Peng, Fei; Jeong, Sinyoung; Gonzalez, German; Marks, Haley; Ho, Alexander; Roussakis, Emmanuel; Krauledat, Petra B.; Hansen, Peter; Evans, Conor L.
Abstract: The glial fibrillary acidic protein (GFAP) is widely established as a traumatic brain injury (TBI) biomarker and can be used in early diagnosis. As essential primary human immune cells, leukocytes are recruited to injured cerebral sites during TBI response, where they can interact with and potentially bind to TBI biomarkers. To date, no studies have demonstrated ultra‐low GFAP binding enumeration on leukocytes. Herein, a dark‐field imaging technique coupled with computational analysis is introduced to quantify GFAP bound to peripheral blood mononuclear cells (PBMCs). Dark‐field microscopy (DFM) with a custom‐written image acquisition software is developed for rapid 3D PBMC imaging by utilizing specific antiGFAP monoclonal antibody functionalized gold nanoparticles (antiGFAP‐AuNPs) as contrast‐generating probes. Subsequently, the developed algorithm is utilized in processing thousands of acquired images for rapid visualization and enumeration of bound antiGFAP‐AuNP on each leukocyte. The proposed method is demonstrates the specific binding of GFAP to the surface of PBMCs on a healthy donor blood. Thereafter, subpopulations of PBMCs with antiGFAP‐AuNP binding are identified with the assistance of fluorescence imaging and DFM imaging, paving a new way to understanding the relationship between TBI and leukocyte classes. Hence, this study offers a rapid and ultra‐sensitive strategy for biomarker assessment following TBI. Abstract : Traumatic brain injury (TBI) without early diagnosis leads to serious disability or even death. A novel gold nanoparticle‐based immunoassay approach coupled with dark‐field microscopy imaging and computational analysis is developed for visualizing and enumerating TBI biomarker (glial fibrillary acidic protein (GFAP)) binding to peripheral blood mononuclear cell (PBMC) surfaces, even classifying subpopulations of PBMCs with high GFAP binding.